An assessment of the pozzolanic potential and mechanical properties of Nigerian calcined clays for sustainable ternary cement blends - Samuel Adesina Adegbemileke; Sylvester Obinna Osuji; Okiemute Roland Ogirigbo (Sustainable Structures)
This study investigates the potential of calcined clays from Nigerian deposits as supplementary cementitious materials. Clay materials were obtained from three sites namely: Ikpeshi, Okpilla and Uzebba. The raw clay samples were then calcined at 700°C and 800°C. Chemical and mineralogical compositions were determined for the raw and calcined clay samples using XRF and XRD respectively. The chemical composition by XRF confirmed these clays as potential pozzolans with SiO2, Al2O3, and Fe2O3 collectively exceeding 70%. XRD analysis identified kaolinite and quartz as major mineral phases in the raw clays, which transformed into metakaolin upon calcination. Thermo Gravimetric Analysis (TGA) indicated varying lime consumption levels among the clays, with Ikpeshi clay displaying the highest pozzolanic reactivity and Uzebba clay the least. Compressive strength investigation on mortar cubes prepared with 50% substitution of Portland cement with the calcined clay and limestone, showed that Ikpeshi clay at 800°C had the best strength performance, with strength activity index of 0.92 (at age 28 days), demonstrating superior pozzolanic potential. Strength development was more significant between 7 and 28 days, indicating the pozzolanic reaction's contribution to long-term strength. However, initial strength at 3 days was lower than the reference Portland cement due to a delayed pozzolanic reaction. XRD analysis of blended pastes revealed typical phases of hydration like portlandite, calcium silicate hydrate phase, strätlingite, and ettringite, with the calcined clay blends showing reduced portlandite content, indicating absorption by the pozzolan's alumina phase.